Generalized Trust and Social Selection Process - Igarashi, Tasuku; Hirashima, Taro (Frontiers in Communication, 2021)
Generalized trust relieves individuals in a socially uncertain situation from dyadic constraints of existing ties and helps them change ties with other individuals to acquire better resources. However, much evidence in the emancipation role of generalized trust as a booster of new relationship formation has been limited to laboratory experiments or cross-sectional surveys. We conducted a four-wave longitudinal survey to test whether individuals high in generalized trust actively switch ties and form open triads in dynamic social networks. Stochastic Actor-Oriented Models were employed to analyze structural changes in advice and personal discussion networks among first-year undergraduates. Results showed the predicted patterns of social selection processes based on generalized trust when the dynamics of the two networks were analyzed simultaneously: only in the advice network, individuals high in generalized trust tended to terminate existing ties, create new ties, and show a decreasing trend toward forming close triads when the degree of local clustering was large. Effective tie-formation strategies of individuals high in generalized trust in a multiplex network structure are discussed.